2013
DOI: 10.4103/0972-124x.113082
|View full text |Cite
|
Sign up to set email alerts
|

A need to educate postmenopausal women of their periodontal health

Abstract: Background:Postmenopausal women have shown proactive willingness to take responsibility for their changing health care needs. The example of osteoporosis is a model that when educated of their bone health status, this cohort follows through with prevention and treatment regimens. Postmenopausal status is considered to be a risk factor for periodontitis. It is known that up to 50% of periodontal disease goes undiagnosed. The goal of periodontal therapy is to prevent tooth loss.Objective:Is there a need, then to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Literature has indicated postmenopausal women as the population most in danger of osteoporosis, hence, it is them who should pay additional attention to their periodontal examination. Disturbingly, the majority of periodontal patients seem to be unaware of their disease, because they correlate oral illness exclusively to the onset of symptoms 57 . This fact points out a necessity to educate people, especially postmenopausal women, on their periodontal management and inform them about the potential benefits that oral health could have on their skeletal well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Literature has indicated postmenopausal women as the population most in danger of osteoporosis, hence, it is them who should pay additional attention to their periodontal examination. Disturbingly, the majority of periodontal patients seem to be unaware of their disease, because they correlate oral illness exclusively to the onset of symptoms 57 . This fact points out a necessity to educate people, especially postmenopausal women, on their periodontal management and inform them about the potential benefits that oral health could have on their skeletal well-being.…”
Section: Discussionmentioning
confidence: 99%
“…It becomes vital that the dentist is equipped with appropriate communication capabilities other than specialty/technical competencies required for creating an entire denture. it became discovered in one of the studies that postmenopausal women have been now not aware of their periodontal health and the risks worried to their systemic fitness and therefore authors suggested growing taskforce comprising of periodontists, generalists, verbal exchange experts 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal disease is not well known among women, although they know the risk factors for developing caries, such as the infrequency of brushing, poor dental technique, and sugary foods. The study showed that most of the patients neither had knowledge about the risk factors nor of all the signs and symptoms, but once it was explained to them, they showed greater interest in self-care and assisted a periodic review by the specialist [24].…”
Section: Diseases and Ethical Considerationsmentioning
confidence: 98%